Job Insecurity: The demotivated employment contract during the Pandemic - Miftahul Jannah; Faruk Faruk (Enrichment : Journal of Management, 2022)
The job insecurity is the employees’ phobia during the Covid pandemic. The company adaptively regulates the employment status to anticipate the collapse through decreasing the number of employee. In this case, it automatically effects on the employees’ demotivation. This research quantitatively describe the effects of job insecurity on the employees’ motivation during the Pandemic. The data periodically collected from the employment contract using the quote-purposive sampling technique in services sector labor. The results, the mean value of employees’ motivation on the first and second six moth was decrease, its t and p values were t=25,591 and p= 0,000 (p<0,05). It means that the employment contract significantly demotivated during the year. The mean value of job insecurity was not significantly differentiate with the t value 3,700 and p= 0,062 (p>0,05). It statistically indicates that since the first six months until the second six months, the employees’ job insecurity was not different. It also can explanatively describes that the completed effect of job insecurity continuously demotivated on the employees’ motivation.